Associations of serum follicle-stimulating hormone and luteinizing hormone levels with fat and lean mass during menopausal transition - Xun Liu; Jingyue Xu; Danmei Wei; Yongjie Chen (Obesity Facts, 2022)
Introduction The association of serum follicle-stimulating hormone (FSH) level with body fat mass remains inconclusive. Furthermore, little was known on the association of luteinizing hormone (LH) with body fat. This study aimed to investigate the associations of serum FSH and LH levels with fat and lean mass in women during menopausal transition. Methods The data analyzed in this study were derived from the National Health and Nutrition Examination Survey from 1999 to 2002. Women aged from 35 to 60 years were eligible. Serum FSH and LH levels were assayed using the Microparticle Enzyme Immunoassay technology. A dual energy X-ray absorptiometry was used to measure body fat mass and lean mass. Fat mass index (FMI) and fat-free mass index (FFMI) were respectively used to assess fat and lean mass. General linear regression was employed to examine the associations of serum FSH and LH levels with FMI and FFMI. Results This study included 1329 women. For the total participants, elevated serum FSH and LH levels were associated with increased FMI (β= 0.004 and 0.007; 95% CI: 0.002, 0.006 and 0.004, 0.010, respectively) and a decreased FFMI (β= -0.004 and -0.007; 95% CI: -0.006, -0.002 and -0.010, -0.004, respectively). Furthermore, the significant associations of serum FSH and LH levels with FMI and FFMI were fully observed in postmenopausal women, especially in a certain range of higher serum FSH and LH quartiles. Conclusion Elevated serum FSH and LH levels were associated with increased body fat mass but a decreased lean mass in postmenopausal women but not in premenopausal women. Furthermore, only higher serum FSH and LH percentiles were associated with fat and lean mass in postmenopausal women.